1994
DOI: 10.1530/eje.0.1300410
|View full text |Cite
|
Sign up to set email alerts
|

Responsiveness to corticotropin-releasing hormone and vasopressin in canine Cushing's syndrome

Abstract: Corticotropin-releasing hormone (CRH) and vasopressin are the most important hypothalamic factors regulating adrenocorticotropic hormone (ACTH) secretion. In this study we have investigated the responsiveness of the pituitary-adrenocortical axis to intravenous administration of CRH or lysine vasopressin (LVP) in 16 control dogs, 22 dogs with pituitary-dependent hyperadrenocorticism and five dogs with hyperadrenocorticism due to an adrenocortical tumor, using doses of CRH and LVP that caused equivalent ACTH res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…These results con®rm earlier reports on in vitro and in vivo studies (39,45) that demonstrated a relative insensitivity of canine corticotrophic tumour cells to stimulation by CRH.…”
Section: Discussionsupporting
confidence: 91%
“…These results con®rm earlier reports on in vitro and in vivo studies (39,45) that demonstrated a relative insensitivity of canine corticotrophic tumour cells to stimulation by CRH.…”
Section: Discussionsupporting
confidence: 91%
“…The ACTH response to combined hypophysiotropic stimulation in dogs with PDH was not different from that in control dogs, but occurred at higher ACTH levels. In studies of the responsiveness to single CRH administration, it was found that, in dogs with PDH, increments in plasma ACTH were similar to (Rijnberk et al 1987) or somewhat lower than (Van Wijk et al 1994) those in control dogs. Although not found in dogs, ACTH hyperresponsiveness to CRH is commonly found in humans with Cushing's disease caused by pituitary microadenomas (Orth et al 1982, Pieters et al 1983, Schrell et al 1987, Fukata et al 1993, although testing in individual patients has revealed hyperresponsiveness, normal responsiveness and even unresponsiveness (Pieters et al 1983).…”
Section: Discussionmentioning
confidence: 97%
“…There is increasing awareness that the sensitivity of the adrenal gland to AVP is an important factor regulating cortisol secretion in patients with ACTH‐independent Cushing's syndrome. An iv injection of LVP evoked a greater response in plasma cortisol levels in dogs with hypercortisolism due to an adrenocortical tumour than in normal animals, in spite of the absence of an increase in plasma ACTH levels ( van Wijk et al ., 1994 ). An im injection of LVP also induced a marked increase in plasma cortisol without any elevation of plasma ACTH levels ( Perraudin et al ., 1995 ).…”
Section: Discussionmentioning
confidence: 99%